Penerapan Sistem Akuntansi Berbasis Akrual Pada Penyusunan dan Penyajian Laporan Keuangan di Pengadilan Tinggi Agama Kupang - Fauziyah Lamaya; Maryono maryono (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2021)
Based on PP No. 71 2010 Article 1 paragraph (8) states that what is meant by the Accrual-Based Government Accounting System (SAP) is SAP which recognizes revenues, expenses, assets, debts, and equity in accrual-based financial reporting, and recognizes revenues, expenditures, and financing in accrual-based financial reporting. reporting on budget implementation based on the basis set out in the APBN or APBD. This study aims to determine the application of accrual-based accounting in the preparation of financial statements at the Kupang Religious High Court. This type of research is descriptive with data collection methods used are observation, interviews and documentation. The results of this study explain that The Kupang Religious High Court uses the accrual basis in the preparation and presentation Balance Sheet, Operational Report, and Report on Changes in Equity and cash basis for the preparation and presentation of the Budget Realization Report. This Financial Report is generated through the Accrual-Based Agency Accounting System (SAIBA) and the State Property Management and Accounting Information System (SIMAK-BMN). The Kupang Religious High Court has succeeded in implementing the accrual-based accounting system well because it is supported by the understanding and ability of the finance staff in the field of government accounting and the competent use of SAIBA, SIMAK-BMN, and other supporting applications.